The effects of cognitive behavioral therapy in women with polycystic ovary syndrome: A meta-analysis - Tang, Rong; Yang, Junlan; Yu, Yanmei; Fang, Yuying (Frontiers in Psychology, 2022)
Background Cognitive behavioral therapy (CBT) has well-characterized benefits in alleviating diseases associated with depression, anxiety, and obesity, resulting in a marked improvement in the patient’s quality of life. There are some studies regarding the effects of CBT on patients with polycystic ovary syndrome (PCOS). However, there is still no report of a meta-analysis for systematic assessment. Objectives This study aimed to evaluate the effectiveness of CBT in improving weight loss, anxiety, depression, life quality, compliance, and pregnancy outcomes in patients with PCOS. Methods Studies regarding CBT related to PCOS in PubMed, Cochrane library, Embase, ClinicalTrials.gov, CNKI, and WANFANG DATA were searched for up to 19 November 2020. A random-effects model was used to perform a meta-analysis. Results Eight trials regarding CBT compared with lifestyle modification and routine treatments were included. No differences in depression (SMD –1.11; 95% CI –2.28, 0.07; P > 0.05), body mass index (BMI) (SMD 0.88; 95% CI –0.94, 2.71; P > 0.05), or overall life quality (SMD 1.24; 95% CI –0.44, 2.92; P > 0.05) were evident between CBT and control groups; however, anxiety (SMD –1.12; 95% CI –2.1, –0.13; P < 0.05) and quality of life in hirsutism (SMD 0.92; 95% CI 0.48, 1.35; P < 0.05) were significantly improved. For secondary outcomes, both patient compliance and pregnancy rate were improved, but no significant change in pregnancy loss rate was identified. Conclusion CBT exhibited obvious advantages in the alleviation of anxiety, improvement of quality of life in hirsutism, and increase of compliance and pregnancy rate in patients with PCOS. Larger and higher-quality randomized controlled trials are needed to clarify the role of CBT in PCOS. Systematic review registration [https://www.crd.york.ac.uk/PROSPERO/], identifier [CRD42021225856].